Perluasan dan Pemerataan Akses Kependidikan Daerah 3T (Terdepan, Terluar, Tertinggal) - Syafii, Ahmad (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2018)
Educating the life of the nation is the task of the state agains it’s people. Education is the noble ideal that has been outlined since this nation was born. With education this nation can contribute with other nations in the world. However, in reality access to education in society has not been evenly distributed. There are still areas, leading and left behind that require a lot of educational touch. Equity is required for access to education so that every citizen who has the same opportunity is educated. Government program ssuch as the SM3T or Bina Daerah program become the chosen strategy. However, it should be supported by the community as a Civil Society. People must also move to develop education.